(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Hotels have embraced a number of green initiatives in response to growing environmental concerns and the worldwide movement towards sustainable development. However, customer awareness and attitudes towards these practices play a major role in the success of these projects. Objective: To examine the consumer awareness level towards sustainable practices exercised in 5-star category hotels of Mumbai and the consumers attitude towards sustainable practices exercised in these hotels. Methodology: The goals of the current study were achieved through the use of descriptive design. The information was gathered from guests who had stayed at Mumbai’s five-star hotels and came from all across India. Convenience sampling was the approach employed in this study to obtain data. A total of 270 respondents were given the questionnaire; 165 of them completed it, and 156 of those answers were deemed legitimate. The main tool used to collect data is the structured questionnaire. Descriptive statistics namely frequency, percentage, mean and standard deviation were calculated Microsoft excel was used for the data analysis. Results: The mean scores indicate varying levels of awareness, with energy conservation initiatives having the highest mean of 3.44 (SD = 1.56) and community engagement and support the lowest at 2.57 (SD = 1.31). The analysis of consumer attitudes towards sustainable practices in 5-star hotels in Mumbai indicates a strong preference for eco-friendly accommodations. The highest mean score of 3.69 (SD = 1.33) was recorded for the preference for sustainable hotels, however, support for community engagement and educational initiatives was, 2.79 (SD = 1.36) and 2.72 (SD = 1.36), respectively. Conclusion: Consumer awareness of sustainable practices in 5-star hotels in Mumbai is strongest in areas like energy conservation, waste management, and water conservation, which are well-implemented and promoted. Consumer generally have a positive attitude towards sustainability initiatives, particularly those that are visible, like energy and water conservation. Others require enhanced visibility and engagement to elevate their perceived importance.